2003
DOI: 10.1124/jpet.102.047217
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ethanol-Induced Liver Injury in Rats by an Agonist of Peroxisome Proliferator-Activated Receptor-γ, Pioglitazone

Abstract: Agonists of peroxisome proliferator-activated receptor (PPAR)-␥ have been shown to reduce tumor necrosis factor-␣ (TNF-␣)-induced insulin resistance. On the other hand, sensitization of Kupffer cells to lipopolysaccharide (LPS) and their production of TNF-␣ are critical for progression of alcoholic liver injury. This study was intended to determine whether pioglitazone, a PPAR-␥ agonist, could prevent alcohol-induced liver injury. Rats were given ethanol (5 g/kg b.wt.) and pioglitazone (500 g/kg) once every 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 33 publications
6
61
1
Order By: Relevance
“…It is also possible that pioglitazone inhibits activation of Kupffer cells independent of adiponectin, because it has also been reported that TZDs inhibit activation of Kupffer cells in a direct manner. 21,22 Taken together, these findings support the hypothesis that the abnormal innate immune responses are critical for the regeneration failure in KK-A y mice.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is also possible that pioglitazone inhibits activation of Kupffer cells independent of adiponectin, because it has also been reported that TZDs inhibit activation of Kupffer cells in a direct manner. 21,22 Taken together, these findings support the hypothesis that the abnormal innate immune responses are critical for the regeneration failure in KK-A y mice.…”
Section: Discussionsupporting
confidence: 76%
“…33 Because TZDs, synthetic PPAR-␥ ligands, not only improve insulin resistance but also inhibit activation of Kupffer cells 21,22 and transactivation of hepatic stellate cells, [34][35][36] these chemicals are believed to be suitable for prevention/treatment of hepatic inflammation and fibrogenesis in NASH. Indeed, a placebo-controlled randomized study has demonstrated the therapeutic efficacy of pioglitazone on NASH in terms of both metabolic and histological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is a nuclear receptor transcriptional factor and plays an important role in many biological processes, including adipogenesis, cell growth regulation, and cell differentiation. Recent studies have found that thiazolidinediones (TZD) such as pioglitazone and troglitazone, a class of anti-diabetic drugs that function as synthetic ligands of PPARγ with high affinity, inhibit neointima formation in vascular smooth muscle cells in association with decreased DNA synthesis, suggesting that PPARγ may be a potential therapeutic target for the treatment of fibrotic diseases [17][18][19] . In the present study, we extended these observations by determining that PPARγ activation results in the inhibition of HSC growth in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of investigation have demonstrated that pioglitazone prevents alcohol-induced liver injury in rodents, implying that upregulation of adiponectin by pioglitazone via activation of PPARc may contribute to its hepatic protective effects (49)(50)(51). Although chronic ethanol feeding did not alter adipose mRNA expression of PPARc in animals (11), PPARc ligand binding function could be suppressed by ethanol.…”
Section: Role Of Pparc In Ethanol Regulation Of Adiponectinmentioning
confidence: 99%